Sarecycline: A Review of Preclinical and Clinical Evidence - Moore AY; Del Rosso J; Johnson JL; Grada A (Dove Medical Press, 2020)
Angela Yen Moore,1,2 James Del Rosso,3,4 Jodi L Johnson,5 Ayman Grada6,7 1Arlington Research Center, Inc., Arlington, TX, USA; 2Baylor University Medical Center, Dallas, TX, USA; 3JDR Dermatology Research/Thomas Dermatology, Las Vegas, NV, USA; 4Touro University Nevada, Henderson, NV, USA; 5Departments of Dermatology and Pathology, Feinberg School of Medicine, Northwestern University, Evanston, IL, USA; 6R&D and Medical Affairs, Almirall (US), Exton, PA, USA; 7Department of Dermatology, Boston University School of Medicine, Boston, MA, USACorrespondence: Angela Yen MooreArlington Research Center, Inc., 711 East Lamar, Suite 200, Arlington, TX 76011, USATel +1 817 795-7546 ext. 328Email acderm@acderm.comAbstract: Sarecycline is a tetracycline-derived oral antibiotic, specifically designed for acne, and is approved by the Food and Drug Administration (FDA) in 2018 for the treatment of inflammatory lesions of non-nodular moderate to severe acne vulgaris (AV) in patients 9 years of age and older. It has been decades since a novel systemic antibiotic was approved to treat AV, a disease that affects up to 90% of teenagers and young adults worldwide and lasts well into adulthood. Sarecycline holds promise to yield fewer side effects than other commonly used broad-spectrum tetracyclines, including minocycline and doxycycline. The narrower spectrum of antibacterial activity of sarecycline, which specifically targets C. acnes and some Gram-positive bacteria with little or no activity against Gram-negative bacteria, suggests not only the potential for reduced emergence of antibiotic-resistant bacterial strains but also less disruption of the human gut microflora. Here, we review the key preclinical and clinical evidence on sarecycline.Keywords: acne vulgaris, antibiotic, narrow spectrum, tetracycline, sarecycline